Reveal Business Model Design: Mental Health Platform for College Students - Hibban, Haafizh; Nuraisyah, Ani; Zulbainarni, Nimmi (Business Review and Case Studies, 2024)
Background: Mental health is a condition in which an individual can realize his potential, can work productively, and be able to contribute to his community. Disruption of mental health can reduce physical condition and affect academic performance. The number of students experiencing mental health disorders is increasing every year. Those with mental health disorders face difficulties in coping with their problems. Purpose: This study aims to identify the problems that students face when their mental health is impaired, design a business model that represents the value of the solutions to be offered, and create a prototype display that contains the features to be offered in the form of an application. Design/Method/Approach: The method used in this research is design thinking. It was found that the most problems faced when students experienced mental health disorders were the existence of bad stigma related to mental health disorders and the fear of getting a negative response when telling stories. Findings/Result: The main feature that we want to offer is online mentoring with psychology students. Solution testing found that the product design had met the needs of the respondent's problems.Conclusion: Based on the problems and assistance desired by the respondents, a business model of reveal created that illustrates the values that will be offered. Reveal is a mental health platform for college students that contains several features, namely mentoring (facilitating users to confiding with peer counselor), narasi (a feature for users to share and discuss related to their mental health problems), mood tracker (feature that records condition of user’s mental health), as well as webinars and articles (a feature that displays information related to mental health).Originality/value (State of the art): This platform is conducted by the audience’s needs and offers so many features that would be a successful implication for helping the student form mental health’s issues.Keywords: business models, design thinking, mentoring, mental health, prototype